P472 Payer addressable burden of Crohn's disease in patients treated with ustekinumab and vedolizumab in the United States. (27th May 2021) - Ghosh, T; Smith, I; Fehr, J; Davidson, J; Fan, T; Candela, N; Tsang, C; Koch, T
Abstract: Background: Vedolizumab (VDZ) and ustekinumab (UST) are treatments for moderate-to-severe Crohn's disease (CD). The payer addressable burden (PAB) is the total allowed cost of care of a national health plan based on an actuarial analysis of all members total cost burden, for a given disease, regardless of any other underlying conditions. We used an actuarial retrospective claims analysis of direct and indirect costs associated with payer allowed resource utilizations to understand the US payer cost burden of the biologic-treated CD population. Methods: Mean annual allowed cost per member with CD in the commercial health plan population was examined from a health plan actuarial and financial perspective. Data were obtained from medical and prescription claims of commercial and Medicare health plan members from Optum's proprietary de-identified Normative Health Information database. Administrative claims data for all commercial members with pharmacy and medical coverage were used to determine medical utilization and medication unit cost patterns for CD treatment for 2017–2019. PAB analysis includes resource utilizations and associated costs among CD patients (pts) whose last biologic agent received in a year was UST subcutaneous (SC) or VDZ intravenous (IV). Costs captured were the total paid by plan and pts for medical or pharmacy claims. ICD-10 diagnosis codes were used to identify prescriptions to be included based on CD diagnosis. Members with diagnostic codes for concomitant ulcerative colitis (UC) were included only if they had more claims for CD than UC. Allowed claims costs, the sum of all medical and pharmacy costs, were categorized as CD-specific PAB and all-cause PAB. Cost per member per month was estimated by dividing total costs by total member enrolled months. Results: In this retrospective claims analysis, more members with CD were treated with VDZ IV than UST SC in 2017 and 2018. Total and CD-related costs were lower with VDZ IV than with UST SC in overall members with CD and biologic-naïve members with CD (Figure 1 ). Both CD-related and all-cause PAB were markedly lower for VDZ IV than UST SC (Figure 2 ). Conclusion: PAB can help payers identify opportunities for cost-saving. For patients with CD, the payer cost burden was lower with VDZ IV than with UST SC. This analysis provides a cross-sectional view of financial burden for US payers in managing members with CD. The analysis did not include longitudinal follow-up of pts for cost difference or adjustment of confounders in biologic-treated pts. The results capture the real-world burden of all forms of clinical practice and resource utilization in treating pts with CD enrolled in a commercial national plan.